The Meaning of “Intermittency” in Criminal Careers - Farrington, David (Journal of developmental and life-course criminology, 2020)
Van Koppen, Rodermund, and Blokland recently published an article in this journal entitled “Waxing and waning: periods of intermittency in criminal careers.” We are concerned that this article will cause confusion in criminal career research because they use the word “intermittency” to refer to time intervals between convictions., We are happy to recognise that their article contributes to knowledge about time intervals between convictions, but we believe that the term “intermittency” should refer to time intervals between two criminal careers when the underlying rate of offending—termed the underlying “criminal inclination” by Van Koppen et al.—is zero., In order to study intermittency, it is important to test probabilistic models of criminal careers., To the extent that there is intermittency, it is desirable to investigate why individuals stop offending, why they maintain a zero-rate of offending for some time, and why they restart offending. We believe that it is also important to study the possibility of waxing and waning in criminal careers, by testing whether the underlying rate of offending during the active criminal career stays constant or varies over time.